2017
DOI: 10.3233/mgc-170234
|View full text |Cite
|
Sign up to set email alerts
|

A green sonochemical synthesis of zinc borates from Zn5(CO3)2·(OH)6

Abstract: In this study by using the precursors of Zn 5 (CO 3 ) 2 •(OH) 6 and H 3 BO 3 , Zn 3 B 6 O 12 •3.5H 2 O type of a zinc borate compound is synthesised. A green sonochemical method of ultrasonic irradiation is used with several parameters such as; reaction temperature and reaction time. Synthesized zinc borate compounds are characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy techniques. Then the surface morphologies are investigated by scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
4
1
0
Order By: Relevance
“…The compounds' XRD patterns with the highest XRD scores are given in Figure 2. The characteristic peaks are in mutual agreement with the studies reported in the literature (Ersan et al, 2016;Kipcak et al, 2014Kipcak et al, , 2015Kipcak et al, , 2016Vardar et al, 2017). In addition, the as-obtained XRD scores were slightly higher than those previously reported in the literature (Table 1).…”
Section: The As-synthesized Zinc Borate Compounds' Xrd Results and Thsupporting
confidence: 90%
See 4 more Smart Citations
“…The compounds' XRD patterns with the highest XRD scores are given in Figure 2. The characteristic peaks are in mutual agreement with the studies reported in the literature (Ersan et al, 2016;Kipcak et al, 2014Kipcak et al, , 2015Kipcak et al, , 2016Vardar et al, 2017). In addition, the as-obtained XRD scores were slightly higher than those previously reported in the literature (Table 1).…”
Section: The As-synthesized Zinc Borate Compounds' Xrd Results and Thsupporting
confidence: 90%
“…The highest reaction yields were procured at 90°C over 55 min for all of the sets, which were calculated to be 98.3 ± 0.2%, 98.4 ± 0.2% and 99.2 ± 0.3% for SET-1, SET-2 and SET-3, respectively. In accordance with the XRD scores, the reaction yields were found to be higher than those previously reported in the literature and significantly higher than those reported by Ersan et al (2016) and Vardar et al (2017).…”
Section: The As-synthesized Zinc Borate Compounds' Xrd Results and Thsupporting
confidence: 82%
See 3 more Smart Citations